Legality of Heir For Non-Muslim Children as a Result of Fornication Under Maqashid Sharia of Jamaludin Athiyya - M. Noor Harisudin; Arvina Hafidzah; Nury Khoiril Jamil; Erni Fitriani; Erisha Najwa Himaya; Khulaila Inda Fikriya (Journal of Islamic Studies and Civilization, 2023)
This article discusses a child born due to fornication with a broken lineage of Muslim father whosechild is a non-Muslim. This article uses a normative juridical method and qualitative analysis. Moreover the study was carried out on the legality of the status of heirs for non-Muslim children born by a fornication out of wedlock, which is viewed under in the perspective of the law in force in the Indonesia law prepective compared with the Maqasid Syariah fil-usrah view of Jamaluddin Athiyya. Regarding the legality of the status of heirs, there are several opinions in the Civil Code providing opportunities for heirsWhile it is clear in the Islamic law, especially the Islamic law of inheritance (Fiqh Mawaris), states that the children born as a result of fornication to be eligible as heirs. The contrast between the two legal systems is fused with the Supreme Court Jurisprudence No. 51.K/AG/1999 and the MUI Fatwa No. 11 of 2012 which states that non-Muslim children as a result of a fornication are not entitled as heirs, but they are eligible to obtain the inheritancethrough a mandatory will (Wasiat Wajibah). Thus, there are still pros and cons on the legal impact of Jurisprudence and Fatwa which are not fully binding. Moreover, Jamaluddin Athiyyah's view of the Maqasid Syariah in terms of the family issueagaints the Supreme Court Decision No. 51.K/AG/1999, No. 368 K/AG/1995, the Constitutional Court Decision No. 46/PUU-VIII/2010 and the MUI Fatwa No. 11 of 2012, concludes although the non-Muslim children born as a result of fornication are not eligible as the heirs. However, the providing a mandatory will has considerably been benefited the child welfare and the family are considered implementing the Islamic law.